Asuhan Kebidanan Pada NY. U Umur 32 Tahun Dengan Faktor Resiko Jarak Kehamilan Terlalu Jauh Di Wilayah Puskesmas Paguyangan Tahun 2023 - Neneng Anisa Rahmawati; Maryam Maryam; Widi Astuti (Institut Nalanda, 2024)
Data released by the World Health Organization (WHO) estimates that 800 women died from complications of pregnancy and childbirth, one of the causes of MMR is high-risk pregnancies such as too far pregnancy distance and maternal age as many as 257 cases, where MMR also increased sharply exceeding cases in 2017 by 88.05% (Central Java Health Office, 2020). Too far pregnancy distance is a pregnancy that is . included in high risk, where the distance of the mother's pregnancy is more than or equal to 10 years with the previous child Methods: The method used in this study was descriptive qualitative method using a comprehensive case study approach. Results: Comprehensive midwifery care on Mrs. U found problems in early pregnancy with TFU that did not match the gestational age. Delivery was done normally vaginally, and the newborn was normal, there was a problem that the baby did not get exclusive breastfeeding. In the postpartum period until birth control, no complications were found but there was a problem during the postpartum period, namely the mother's breast milk was small. Conclusion: Comprehensive Midwifery Care that has been carried out on Mrs. U with Risk Factors for Too Far Pregnancy Distance is in accordance with midwifery care and no complications occur.